Pengembangan Sistem Informasi Berbasis Android pada SMA Negeri 17 Gowa - M. Nurmuhajirin Surahman; Muhammad Yusuf Mappeasse; Ninik Rahayu Ashadi (Progressive Information, Security, Computer, and Embedded System, 2025)
This research aims to (1) Knowing the results of testing on the development of school information systems at SMA Negeri 17 Gowa, and (2) assess the effectiveness and practicality of the developed school information system at SMA Negeri 17 Gowa. This type of research is Research & Development (R&D). The development was carried out using the prototype model. The results obtained from the research are a system that can be used by the community and students of SMA 17 Gowa. This system has undergone software testing using ISO 25010, encompassing several aspects such as (1) Functional Suitability, achieving a score of 95.83% (very suitable); (2) Performance Efficiency, based on software testing using performance overlay tools, the average GPU and UI (CPU) usage indicators showed a green line, indicating normal results; (3) Compatibility, where multiple applications running simultaneously showed that both could operate well; (4) Usability, tested with 30 respondents using a random sampling method, achieved a score of 86.58%, categorized as very good; (5) Reliability, in tests covering good operational levels of the system and ease of access; (6) Maintainability, the testing showed that the system is in a very good category; (7) Portability, in this aspect, testing on several types of smartphones with different Android versions ran well without issues; (8) Security, testing yielded a security score of 65/100. The conclusion from these results is that the software has passed system evaluation and is deemed suitable, ready to be handed over to users and put into use.